الخدمة الاجتماعية في فلسطين: ما بين واقع التعليم وغياب الممارسة المهنية - شبيطة، زردة حسن; عبدالرازق، كوثر ربحي (المركز القومي للبحوث غزة, 2020)
استهدفت ورقة العمل الحالية التعرف على واقع الخدمة الاجتماعية في فلسطين، من حيث تعليمها وواقع ممارستها المهنية، ضمن المؤسسات الاجتماعية العاملة في فلسطين، حيث قامت الباحثتان بتناول مجموعة من المحاور الأساسية، من خلال عرض، وتوضيح شمولي لمفهوم تعليم وممارسة الخدمة الاجتماعية، وواقع نشأة تعليمها في فلسطين، وحاجة المجتمع الفلسطيني إلى وجودها، للوصول إلى كيفية ممارستها في فلسطين. وتوصلت الباحثتان من خلال التحليل والنقاش، إلى أن هناك غياب للممارسة المهنية العملية في تلك المؤسسات الفلسطينية، ويرجع ذلك إلى العديد من الأسباب منها؛ لا يوجد في هذه المؤسسات ممارسة متخصصة؛ حيث إن هذه المؤسسات تمارس العمل المهني غير معتمدة على أطر نظرية، وبدون معرفة بطرق التدخل المهني، وضعف وندرة في ممارسة العمل مع الحالات الفردية، والعمل مع الجماعات، والمجتمعات، لغياب الإمكانيات المادية والبشرية. في نهاية الورقة العلمية، تم طرح العديد من التوصيات من قبل الباحثتين في ظل غياب الممارسة المهنية؛ تمثلت بضرورة العمل على توسيع قاعدة الاعتماد على البحوث، والدراسات الميدانية، واستخدام نتائجها في رسم الخطط، والمشاريع الاجتماعية في المجتمع الفلسطيني، بالإضافة إلى زيادة عدد أعضاء هيئة التدريس المتخصصين في الجامعات الفلسطينية، بتعليم الخدمة الاجتماعية وفق الأسس والأساليب العلمية الحديثة، بما يساعد على إمداد المتعلمين، بأهم الطرق العلمية للممارسة المهنية، وينقلها الطلبة، إلى تلك المؤسسات الاجتماعية، لترتقي بأسلوب عملها، وممارستها ضمن الواقع الفلسطيني، الذي هو بأمس الحاجة إلى التدخل المهني الصحيح.
The current working paper aimed to identify the reality of social service in Palestine, in terms of its education and the reality of its professional practice, within the social institutions operating in Palestine, where the two researchers addressed a set of basic axes, through a comprehensive presentation and clarification of the concept of education and practice of social service, and the reality of the origin of its education In Palestine, and the need for Palestinian society to exist, to find a way to practice it in Palestine. The two researchers concluded, through analysis and discussion, that there is an absence of practical professional practice in these Palestinian institutions, due to many reasons, including :There is no specialized practice in these institutions .Whereas, these institutions practicing professional work are not dependent on theoretical frameworks, and without knowledge of methods of professional intervention, and the weakness and scarcity in the practice of working with individual cases, and working with groups and societies, in the absence of material and human capabilities. At the end of the scientific paper, several recommendations were made by the two researchers in the absence of professional practice; It was represented by the necessity of working to expand the base of relying on research and field studies, and using its results in drawing plans and social projects in the Palestinian community, in addition to increasing the number of faculty members in Palestinian universities who specialize in teaching social service in accordance with the foundations and modern scientific methods, including helping this to Providing learners with the most important scientific methods of professional practice, and students transfer them to these social institutions, to improve their work style, and practice them within the Palestinian reality, which is in urgent need of proper professional intervention.
Keywords: الخدمة الاجتماعية -- المؤسسات الاجتماعية -- فلسطين